The European Convention on Human Rights and the employment relation (Oxford, 2013)
"The accession by the European Union to the European Convention on Human Rights (ECHR) has opened up new possibilities in terms of the constitutional recognition of fundamental rights in the EU. In the field of employment law it heralds a new procedure for workers and trade unions to challenge EU law against the background of the ECHR. In theoretical terms this means that EU law now goes beyond recognition of fundamental rights as mere general principles of EU law, making the ECHR the 'gold standard' for fundamental (social) rights.